OCCASIONAL PHRASEOLOGICAL SYNONYMY - Mena Martinez, Flor (International Journal of English Studies, 2009)
Just from one type of formal modification, i.e. lexical substitution, various semantic relationships between the the original phraseological unit (PhU) and the modified occurrence (MPhU) can be derived. We cannot rely on the semantic connection between the elements which take part in the substitution to describe and identi@ this semantic link. This is so because many times there is no semantic connection between the lexemes involved in the process. The key to interpret the kind of semantic relationship has to be extracted from the contextual clues. Following a cognitive approach, the purpose of this paper is doublefold. First, we focus on the analysis of one type of semantic relation, the synonymy, of creative variations of proverbs; and second, we check the validity of the cognitive approach to identify the procedures, transformations and changes which take part in the process of formal modification which ends in the generation of a synonymous paremiological unit.